Meningkatkan Hasil Belajar Siswa Menggunakan Model PBL dengan Menggunakan Media Gambar di Fase C Kelas V SDN 106821 Bandar Baru - Santalia Veronika Br Perangin-angin; Dicky Aprianto; Hedwigis Dian Permatasari (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The results of initial observations regarding student learning outcomes in the learning process at SD Negeri 106821 Bandar Baru, especially in the subjects of Catholic religion and character, are very poor, as are students who are less motivated and lack concentration in the learning process. The aim of this research is to improve student learning outcomes by using the problem based learning model phase C for class 5 SD Negeri 106821 Bandar Baru. This research uses a classroom action research (PTK) design which consists of 4 stages, namely planning, implementation, evaluation and reflection. The subjects of this research were 4 students in class 5 phase C, 3 boys and 1 girl. The data collection technique was carried out by 1. Observation with indicators of the Pancasila student profile of the dimension of mutual cooperation with indicators of respect for fellow friends, cooperation, solidarity and empathy, deliberation to reach a consensus, and mutual help. 2. Cognitive learning outcomes tests with targets of proficient, competent, decent, and just developing. The results of the research showed that there was an increase in the P3 observation aspect in cycle 1 with an average of 60% and an increase in cycle 2 with an average of 70%. Meanwhile, in the learning test aspect, cycle 1 produced an average score of 73.75 and cycle 2 produced an average score of 88.75. It can be concluded that the PBL learning model can improve learning outcomes and develop student character.